Efficacy of silicone as a dowel impression material - Howlader, Tariq Hasan; Alam, Mohammad Khursheed; Sultana, Alia (Bangladesh Journal of Medical Science, 2012)
Background: Different types of impression materials and different procedures or methods have been introduced in Dentistry for preparing dowel crown. Materials and Methods: Injection technique with silicone impression materials are being extensively used by the materials to get an accurate impression. But whether this material neither ensures similar accuracy nor produces absolute accuracy. This study evaluate silicone impression material was efficient enough to produce nearest to actual intraradicular surface reproduction by assessing the void formation and dimensional accuracy. Conclusion: By assessing all the parameters the silicone impression material was proved to be the efficient for intraradicular surface reproduction. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12614 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12